2013
DOI: 10.1111/pin.12042
|View full text |Cite
|
Sign up to set email alerts
|

POU domain transcription factor BRN2 is crucial for expression of ASCL1, ND1 and neuroendocrine marker molecules and cell growth in small cell lung cancer

Abstract: BRN2 is a developmental neural cell-specific POU domain transcription factor and is crucial for cell lineage determination. We investigated the importance of BRN2 in the expression of the lineage-specific transcription factors (achaete-scute homolog-like 1 (ASCL1) and NeuroD1 (ND1)) and neural/neuroendocrine marker molecules (neural cell adhesion molecule 1 (NCAM1), synaptophysin (SYP) and chromogranin A (CHGA)) in small cell lung cancer (SCLC) using cultured lung cancer cells. All examined SCLC cell lines exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 48 publications
1
43
0
Order By: Relevance
“…Interestingly, a genome-wide chip assay has shown that ASCL1 directly binds Tagln3 promoter [50]. ASCL1 and CHGA have the same overexpression profile in small-cell lung cancer [51]. Although we have no in vitro or in vivo evidence that HES5, HEY1, ASCL1 and/or NHLH1 directly binds to or regulates the expression of Chga , Chrdl1 and Robo2 genes, we have found several well conserved putative HEY1-, and ASCL1- and NHLH1-binding sequences located within the 600 bp around their transcription start sites.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a genome-wide chip assay has shown that ASCL1 directly binds Tagln3 promoter [50]. ASCL1 and CHGA have the same overexpression profile in small-cell lung cancer [51]. Although we have no in vitro or in vivo evidence that HES5, HEY1, ASCL1 and/or NHLH1 directly binds to or regulates the expression of Chga , Chrdl1 and Robo2 genes, we have found several well conserved putative HEY1-, and ASCL1- and NHLH1-binding sequences located within the 600 bp around their transcription start sites.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the POU domain-containing family of transcription factors contains multiple mammalian members divided into 6 classes, which can be expressed broadly or in a cell-specific manner and involved in regulators of cell fate decisions of many different lineages. BRN2, which is encoded by the POU3F2 gene in humans,17 is expressed predominantly in the central nervous system (CNS) and has been implicated with tumorigenesis in melanoma and lung cancer 1822. What’s more, the Pbx/POU binding site has been demonstrated to be present in the FABP 7 promoter in humans, and Pbx/knotted homeobox 1 (PKNOX1) is bound to the Pbx / POU site at the FABP 7 promoter to regulate FABP 7 transcription 23.…”
Section: Introductionmentioning
confidence: 99%
“…The only other gene located within the deleted 6q16.1–16.2, BRN2 , is a leading regulator of neuronal differentiation, mainly expressed during development in cells originated from neural crest. BRN2 is known as an oncogene in melanomas (originating from melanocytes derived from neural crest cells) 24 , neuroendocrine small cell lung cancers (SCLCs) 25 , where its overexpression correlates with cell invasiveness and metastatic capacity 24 , and lethal neuroendocrine prostate cancers 26 . In our clinical samples, only FBXL4 but not BRN2 expression correlated with prostate cancer progression.…”
Section: Discussionmentioning
confidence: 99%